2016
DOI: 10.4103/1319-3767.195560
|View full text |Cite
|
Sign up to set email alerts
|

p16 protein is upregulated in a stepwise fashion in colorectal adenoma and colorectal carcinoma

Abstract: Background/Aims:p16 is tumor suppressor gene acting as a cell cycle regulator. The present study was conducted to compare p16 expression in normal, dysplastic, and malignant colonic mucosae, and to explore its relation to clinicopathological variables and follow-up data in colorectal carcinoma (CRC).Patients and Methods:Tissue microarrays were performed from 25 normal colonic mucosae, 41 colonic adenomas, and 191 CRC, with corresponding 50 nodal metastases. Immunohistochemistry was performed using anti-p16 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…P15 and P16 have also been identified as tumor-suppressive proteins in CRC [49, 51]. In this study, we reported that overexpression of P57 and KLF2 can inhibit proliferative ability of CRC cells, and cause G1/G0 phase arrest.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…P15 and P16 have also been identified as tumor-suppressive proteins in CRC [49, 51]. In this study, we reported that overexpression of P57 and KLF2 can inhibit proliferative ability of CRC cells, and cause G1/G0 phase arrest.…”
Section: Discussionmentioning
confidence: 60%
“…We also reported that lncRNA HOXA-AS2 mediated CRC proliferation partly through inhibiting P21 and KLF2 expression [30]. In addition, the effects of P15 and P16 on CRC progression have been studied previously [49-51]. …”
Section: Resultsmentioning
confidence: 99%
“…P16 is a tumor suppressor gene with function in cell cycle regulation. The abnormal function of this gene is thought to be among the earliest events involved in the progression of carcinogenesis [13][14][15][16][17].…”
Section:  Introductionmentioning
confidence: 99%
“…Among the 41 studies, 9 studies with 1731 patients were performed to analyze the correlation between p16 protein expression and OS of CRC, and 20 studies with 755 controls and 1733 cases were included for the analysis of risk of CRC. [ 26 66 ] In addition, clinical information was extracted to analyze the association between p16 protein expression and clinicopathological features of CRC. These characteristics of eligible studies are presented in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%